2019
DOI: 10.1111/gwao.12424
|View full text |Cite
|
Sign up to set email alerts
|

In God's name: Calling, gender and career success in religious ministry

Abstract: Funding information Church of England This article uses a gender lens to examine how people with a calling conceptualize what career success means to them, that is, what work-related outcomes they seek to accomplish in their career. Qualitative data were gathered from ministers of religion working for the Church of England, an organization where gender discrimination is deeply embedded. The findings show that people with the same calling may conceptualize their own career success in quite different ways. Many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…They have realized that only work for economic reward neither can help them to find the real meaning of the job nor can let them focus on innovation activities. Furthermore, the attitude that regard the work as a task may make employees difficult to arouse work enthusiasm, which is detrimental to their subjective well-being and mental health (Allan and Duffy, 2013; Hagmaier and Abele, 2012; Sturges, 2019). Therefore, it is essential to study the relationship between career calling and employee behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…They have realized that only work for economic reward neither can help them to find the real meaning of the job nor can let them focus on innovation activities. Furthermore, the attitude that regard the work as a task may make employees difficult to arouse work enthusiasm, which is detrimental to their subjective well-being and mental health (Allan and Duffy, 2013; Hagmaier and Abele, 2012; Sturges, 2019). Therefore, it is essential to study the relationship between career calling and employee behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the traditional career narrative that schematically describes a career in the ministry along the lines of other organizational careers-from leading smaller congregations or associate pastor positions, through leadership positions in larger congregations, to higher leadership positions in the church-is not gender-neutral either. In the case of male pastors, we are more likely to encounter attitudes that interpret a career path as a series of progressions to increasingly better positions, which is similar to the attitudes found in secular occupations (Nesbitt 1997), and which understands vocational success essentially in terms of leadership (Sturges 2019). Charlton (2000) argues that women pastors often refuse to interpret their pastoral careers in this framework, instead emphasizing the importance of faith, vocation, and work being done well as an alternative career narrative.…”
Section: Differences In Male and Female Conceptions Of Calling Career...mentioning
confidence: 94%
“…Experiencing a call strengthens women pastors' willingness to accept difficulties and it also enhances their ability to cope with them (Greene and Robbins 2015). Calling is, therefore, not a gender-neutral concept, either regarding the way it is experienced and pursued or in terms of career outcomes (Sturges 2019).…”
Section: Differences In Male and Female Conceptions Of Calling Career...mentioning
confidence: 99%
“…Gender was added as a control variable, since studies revealed that gender significantly influenced job burnout [52], career calling [53], and emotional intelligence [54]. Similarly, the control variables also included age, as age also had an effect on job burnout [55], career calling [56,57], and emotional intelligence [58].…”
Section: Control Variablesmentioning
confidence: 99%